WNK1-dependent water influx is required for CD4+ T cell activation and T cell-dependent antibody responses - Joshua Biggs O’May; Lesley Vanes; Leonard L. de Boer; David A. Lewis; Harald Hartweger; Simone Kunzelmann; Darryl Hayward; Miriam Llorian; Robert Köchl; Victor L. J. Tybulewicz (Nature Communications)
Abstract Signaling from the T cell antigen receptor (TCR) on CD4+ T cells plays a critical role in adaptive immune responses by inducing T cell activation, proliferation, and differentiation. Here we demonstrate that WNK1, a kinase implicated in osmoregulation in the kidney, is required in T cells to support T-dependent antibody responses. We show that the canonical WNK1-OXSR1-STK39 kinase signaling pathway is required for TCR signaling in CD4+ T cells, their subsequent entry into the cell cycle, and suppression of the ATR-mediated G2/M cell cycle checkpoint. We show that the WNK1 pathway regulates ion influx leading to water influx, potentially through AQP3, and that water influx is required for TCR-induced signaling and cell cycle entry. Thus, TCR signaling via WNK1, OXSR1, STK39 and AQP3 leads to water entry that is essential for CD4+ T cell proliferation and hence T cell-dependent antibody responses.